The Visionary Preaching of Juana de la Cruz (1481-1534) : Ritual, Revelation, and Collective Writing - Acosta-García, Pablo (Late Antiquity and Medieval Studies E-Books Online, Collection 2025., 2025)
Step into the world of 16th-century Castile, where a devout community of Franciscan women preserved the public preaching of their visionary abbess, Juana de la Cruz (1481-1534), through writing. This groundbreaking book uncovers how her sermons were recorded, explores the materiality of the surviving codices, and reveals their role in the controversial censorship and blocking of Juana's canonization. Tracing the rich tradition of the liturgical vision (12th-16th centuries), it delves into female literacy and the creation of collective knowledge in female religious houses around Europe. Featuring rare insights and fresh evaluations of historical texts, this volume illuminates the intersection of female prophetic preaching, community, and the written word at the end of the Middle Ages.